2015
DOI: 10.1002/jat.3169
|View full text |Cite
|
Sign up to set email alerts
|

Directional and color preference in adult zebrafish: Implications in behavioral and learning assays in neurotoxicology studies

Abstract: The zebrafish (Danio rerio) is a useful vertebrate model organism for neurological studies. While a number of behavior and learning assays are recently reported in the literature for zebrafish, many of these assays are still being refined. The initial purpose of this study was to apply a published T-maze assay for adult zebrafish that measures how quickly an organism can discriminate between different color stimuli after receiving reinforcement to measure learning in a study investigating the later life impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 29 publications
0
43
1
Order By: Relevance
“…Although the Avdesh group 4,9 used colors on the bottom, all other investigators used colors on the walls. [10][11][12][13] The clearest discriminations are observed when yellow zones are compared with blue zones. Almost all animals immediately swim into the blue zone.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the Avdesh group 4,9 used colors on the bottom, all other investigators used colors on the walls. [10][11][12][13] The clearest discriminations are observed when yellow zones are compared with blue zones. Almost all animals immediately swim into the blue zone.…”
Section: Discussionmentioning
confidence: 90%
“…Some authors report a clear blue aversion, 4,9 whereas others report a blue preference. [10][11][12][13] Again the location of the color is of critical importance. Although the Avdesh group 4,9 used colors on the bottom, all other investigators used colors on the walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, BarbaEscobedo and Gould (2012) found that zebrafish were more likely to enter a blue rather than orange box (as assessed by initial preference) while Bault et al (2015) found that zebrafish preferred colours of shorter wavelength. These and the current results differ from the findings reported by Avdesh et al (2012) who used both a place preference procedure similar to that used in the current study and a T-maze procedure.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…4 introduced assays of zebrafish learning and behaviour that have been used in testing the neurotoxicity of drugs (Avdesh et al, 2012;Bault et al 2015;Emran et al, 2008;Li et al, 2014;Parng et al, 2007;Schloss, 2015). Natural colour preference is a major factor by which learning, memory, decision-making and functionality of the zebrafish visual system can be assayed.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%